Quantitative Fractography - Well Spring of Intimate Knowledge in Fatigue Crack Growth History - Jiri Kunz; Jan Siegl; Ivan Nedbal (Communications - Scientific letters of the University of Zilina, 2009)
Quantitative fractography of fatigued structure parts can offer very useful and valuable information on the fatigue process. One of main contribution of this experimental method is a detailed description of fatigue crack growth in time and in space. The fractographic reconstitution of fatigue process history is conditioned by the existence and detectability of a fractographic feature characteristics of which is correlated with the fatigue crack growth rate. In the paper presented, three various fractographic features are used for the fractographic reconstitution – striations (in the case of constant amplitude loading), beach marks (for simple program loading) and special inserted fracture marks (for complex program loading). All three methods described are illustrated on case studies, all from the area of testing and development of aircraft structure parts.